(untitled) (World Science, 2021)
Disorders in the system of neurohumoral regulation, gastrointestinal peptide hormones, such as cholecystokinin-pancreozymin (CCK-PZ), which also acts as a neurotransmitter, are of great importance in the development of the biliary tract pathology. The influence of CCK-PZ on the gallbladder function in patients with chronic acalculous cholecystitis in combination with non-alcoholic fatty liver disease (NAFLD) and Stable ischemic heart disease (SIHD) remains unexplored.We have examined 60 patients with chronic acalculous cholecystitis, among which patients with concomitant NAFLD and SIHD or without comorbidity were distinguished. The lipid spectrum of the blood was determined for all patients, the level of CCK-PZ in the blood serum was determined by the enzyme immunoassay using reagents made by Peninsula Laboratories Inc (USA). A polypositional ultrasound examination of the gallbladder was performed, as well as a fractional multiple moment duodenal intubation. It was found that the combination of chronic acalculous cholecystitis with NAFLD and SIHD is manifested by a significant violation of lipid metabolism, dyslipidemia, an increase in cholesterol of proatherogenic lipoprotein fractions and a deficiency of high density lipoproteins. A decrease in the level of cholecystokinin-pancreosimin in patients with chronic acalculous cholecystitis leads to a decrease in the contractility of the gallbladder and an increase in the tone of the sphincter of Oddi. An increase in the level of triacylglycerols and total cholesterol leads to an increase in the flow of lipids into the wall of the gallbladder, which is manifested by its thickening and hypotension of the gallbladder.